Lessons learned from the investigation and management of an outbreak of Shigella flexneri associated with a restaurant in London, 2019–2020. (April 2022) - McLarty, K.; Paranthaman, K.; Jenkins, C.; Sedgwick, J.; Crawley-Boevey, E.
Abstract: Background: Foodborne outbreaks of Shigella flexneri infection are uncommon in the UK. In November 2019, the United Kingdom Health Security Agency investigated an outbreak of S. flexneri associated with a fast-food restaurant in London. Methods: Epidemiological investigations included case ascertainment and interviewing suspected cases using enhanced surveillance questionnaires. Whole-genome sequencing (WGS) was used for characterisation of human isolates. Environmental investigations included a review of food safety processes at the implicated restaurant, administration of exposure questionnaires and stool sampling of staff. Results: Between November 2019 and February 2020, 17 cases were confirmed as part of the outbreak by WGS in London. Among these, 15 were linked to the implicated restaurant. A review of the food safety processes at the restaurant was satisfactory. Despite initial suboptimal coverage of stool screening of staff, all staff members working at the restaurant during the sampling period were screened and an asymptomatic food handler tested positive for S.flexneri with the outbreak WGS profile. The individual underwent microbiological clearance, and no further cases were reported. It was not possible to confirm the direction of transmission for the community cases or the staff member. Conclusion: We report an outbreak of S. flexneri in a fast-food restaurant in London with previous inspection ratings indicating good compliance with food safety and hygiene standards. WGS was crucial in identifying cases linked to the outbreak. This outbreak highlights the importance of prompt testing of food handlers in outbreaks suspected to be associated with food businesses.